Quality Matters Review of LIB 2210: Applying the QM Rubric for Higher Education to an Information Literacy Course. - Sheets, Laura A.; Barry, Maureen; Bosch, Eileen K. (Journal of Library & Information Services in Distance Learning)
This article discusses the use of the Quality Matters Rubric for Higher Education, 6th ed. to self-review an asynchronous information literacy course. In this instance, the authors acted as reviewers and subject matter experts (SME). The Rubric proved to be a useful tool that encompasses several instructional design best practices. After the official self-review period, the QM Rubric influenced the enhancement and updates to the course. The authors recommend more use of the QM Rubric by teaching librarians, collaboration with instructors going through a QM Review, and training for online teaching in Library and Information Science graduate programs.